Relationship between subclinical hypothyroidism and serum osteoprotegerin level in type 2 diabetic patients - Eman H El-Adawy; Gehan A Shaker; Amal Seleem (SpringerOpen, 2017)
Background Subclinical hypothyroidism (SCH) and osteoprotegerin (OPG) are associated with higher risks of cardiovascular disorders in patients with type 2 diabetes mellitus (T2DM). It is unknown whether diabetic patients with SCH have elevated OPG compared with those with euthyroid and, if so, whether SCH independently associated with OPG level. Objective The objective was to study the association between SCH and serum OPG level among Egyptian adults with newly diagnosed T2DM. Patients and methods One hundred and fifty patients with newly diagnosed T2DM and 150 healthy controls matched for sex and age were included in the study. Serum OPG, thyroid-stimulating hormone (TSH), free thyroxine, free triiodothyronine, blood glucose, lipid profile, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), and anthropometric measurements were assessed for all participants. Results The prevalence of SCH and elevated level of OPG in the diabetic patients were higher than healthy controls (17.3 vs. 4%, P<0.001; and 14 vs. 4.7%, P=0.02; respectively). Diabetics with SCH demonstrated significantly higher HOMA-IR, serum TSH, and OPG compared with diabetics without SCH. Serum TSH was significantly correlated with total cholesterol (P=0.05), fasting insulin (P=0.01), HOMA-IR (P=0.01), and OPG (P=0.005). Moreover, serum OPG was correlated with waist circumference (P=0.01), fasting insulin (P=0.05), and HOMA-IR (P=0.02). Multiple logistic regression analysis revealed that SCH was associated with serum level of OPG independently of the other significant variables (β=2.49, P=0.01). Conclusion T2DM patients with SCH demonstrate higher level and independent association with serum OPG than those with euthyroid. This result might add new information about the causal relationship between SCH and cardiovascular disorders in such a population.